The Christian church - Hughes, Anne; Gilbride, Juliana (CCEA GCSE Religious Studies, 2022)
Revised edition of the ‘Christianity’ textbook (ISBN 978-1-906578-32-9). It covers Units 1 and 2 of the CCEA GCSE Religious Studies specification, offering the choice of studying: The Christian Church through a study of the Catholic Church and the Protestant Church; or The Christian Church with a focus on either the Catholic Church or the Protestant Church. Includes exercises, questions and a glossary.